The complexity of apoptotic cell death in mollusks: An update. Issue 1 (September 2015) - Romero, A.; Novoa, B.; Figueras, A.
Abstract: Apoptosis is a type of programmed cell death that produces changes in cell morphology and in biochemical intracellular processes without inflammatory reactions. The components of the apoptotic pathways are conserved throughout evolution. Caspases are key molecules involved in the transduction of the death signal and are responsible for many of the biochemical and morphological changes associated with apoptosis. Nowadays, It is known that caspases are activated through two major apoptotic pathways (the extrinsic or death receptor pathway and the intrinsic or mitochondrial pathway), but there are also evidences of at least other alternative pathway (the perforin/granzyme pathway). Apoptosis in mollusks seems to be similar in complexity to apoptosis in vertebrates but also has unique features maybe related to their recurrent exposure to environmental changes, pollutants, pathogens and also related to the sedentary nature of some stages in the life cycle of mollusks bivalves and gastropods. As in other animals, apoptotic process is involved in the maintenance of tissue homeostasis and also constitutes an important immune response that can be triggered by a variety of stimuli, including cytokines, hormones, toxic insults, viruses, and protozoan parasites. The main goal of this work is to present the current knowledge of the molecular mechanisms of apoptosis in mollusks and to highlight those steps that need further study. Graphical abstract: Highlights: Apoptosis in mollusks is similar in complexity to apoptosis in vertebrates. It has unique features related to the response to environmental changes and pathogens. The complex apoptotic process could be related to the mollusks ecological success. This knowledge allow us to develop new tools for the evaluation of genotoxic risk.